2010
DOI: 10.2109/jcersj2.118.300
|View full text |Cite
|
Sign up to set email alerts
|

SrTiO3-based sensors for in situ monitoring of trace levels of oxygen

Abstract: Semiconductive dielectric SrTiO 3 thin films are promising candidates for the in situ monitoring of trace levels of oxygen in semiconductor manufacturing processes. Highly sensitive oxygen sensors were prepared by atomic-layer deposition (ALD) or pulsed-laser deposition (PLD) of SrTiO 3 ; however, there was a problem with ALD-SrTiO 3 that surface defects, such as SrO surface segregation with a minor contribution from SrO 2 , affected the detection below an oxygen concentration [P O2 /(P O2 + P He )] of 1.1 © 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 10 publications
2
22
1
Order By: Relevance
“…Spectroscopic and electrophysical studies confirm the room-temperature reversible interaction of SrTiO 3 single crystals and thin films with O 2 , and give evidence for the existence of the ionosorbed oxygen species, 24 the formation of the electron-depleted layer in air, 25 and the modulation of the surface conductivity on going from vacuum to ambient air. 26 The latter studies show that the surface conductance of n-doped SrTiO 3 thin films drops by orders of magnitude for pO 2 > 10 À2 torr, which is consistent with the $1 torr threshold for the modulation of the Schottky barrier height, leak current density, and RS ratio highlighted by Figs. 3(a), 3(c), and 3(d).…”
supporting
confidence: 76%
“…Spectroscopic and electrophysical studies confirm the room-temperature reversible interaction of SrTiO 3 single crystals and thin films with O 2 , and give evidence for the existence of the ionosorbed oxygen species, 24 the formation of the electron-depleted layer in air, 25 and the modulation of the surface conductivity on going from vacuum to ambient air. 26 The latter studies show that the surface conductance of n-doped SrTiO 3 thin films drops by orders of magnitude for pO 2 > 10 À2 torr, which is consistent with the $1 torr threshold for the modulation of the Schottky barrier height, leak current density, and RS ratio highlighted by Figs. 3(a), 3(c), and 3(d).…”
supporting
confidence: 76%
“…The shoulder peak on the higher binding energy side of the main O 1s peak at approximately 532.5 eV originates from the adsorption of hydroxyl groups on the surface . The Sr 3d, Ti 2p, and O 1s peak positions were found to be in agreement with the Ti–O and Sr–O binding energies in SrTiO 3 after annealing confirming the formation of strontium titanate …”
Section: Resultsmentioning
confidence: 54%
“…24 The Sr 3d, Ti 2p, and O 1s peak positions were found to be in agreement with the Ti−O and Sr−O binding energies in SrTiO 3 after annealing confirming the formation of strontium titanate. 25 Table 1 shows the EDS chemical composition of the SrTiO 3 NTAs at two different areas on the surface and along the nanotubes shown in the FESEM images in the table. As seen in the FESEM images, the surface of the nanotubes is composed of nanocubes oriented around the nanotubes, and the walls of the nanotubes are composed of brick-like morphology oriented along the longitudinal direction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The oxygen concentration (more precisely, fugacity) [¼P O2 =ðP O2 þ P He Þ, where P O2 and P He are the partial pressures of oxygen and helium, respectively] was controlled by an oxygen-pump-based gas-calibration system. [2][3][4][5][6][7] The oxygen concentration was validated by using H 2 -O 2 -H 2 O buffer gas. It has been reported that the correction of the electronic transport number is not required.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, [1][2][3][4][5][6][7] we reported that SrTiO 3 -based thin films can be used to detect trace amounts of oxygen at room temperature.…”
Section: Introductionmentioning
confidence: 99%